Topology of fracture networks - Andresen, Christian A.; Hansen, Alex; Le Goc, Romain; Davy, Philippe; Hope, Sigmund M. (Frontiers in Physics, 2013)
We propose a mapping from fracture systems consisting of intersecting fracture sheets in three dimensions to an abstract network consisting of nodes and links. This makes it possible to analyze fracture systems with the methods developed within modern network theory. We test the mapping for two-dimensional geological fracture outcrops and find that the equivalent networks show small-world characteristics and are dissasortative. By analyzing the Discrete Fracture Network model, which is used to generate artificial fracture outcrop networks, we also find small world networks. However, the networks turn out to be assortative.